Calculation of the Maximum Flight Cycle of the Cessna 208B Aircraft on the Commuter Route Network in Kalimantan - Adri, Raiztama; Mufti Arifin; Syarifah Fairuza (Jurnal Teknologi Kedirgantaraan, 2025)
Regional flights in Indonesia, particularly in Kalimantan, play a crucial role in connecting remote areas and supporting local economic activities. This analysis focuses on the maximum number of flight cycles that can be operated by the Cessna 208B turboprop aircraft using various strategies within the commuter route network in Kalimantan. The objective of this research is to calculate the maximum number of flight cycles based on differences in payload influenced by several flight strategies, utilizing the Cessna 208B Information Manual. The research process begins with identifying commuter routes in Kalimantan, collecting data from the Pilot Operating Handbook for the aircraft, fuel consumption, and flight performance at specific altitudes. Among the three strategies identified, the full tank strategy allows the aircraft to carry 1,018 kg of fuel at the start of the flight, with remaining passenger weight from the Maximum Take-Off Weight, resulting in 4 flight cycles. The full passenger strategy, with 11 passengers, allows the aircraft to carry 589 kg of fuel without refueling, yielding 2 flight cycles. By employing a refueling strategy at each airport, the aircraft can carry varying amounts of fuel, resulting in 8 flight cycles. It can be concluded that the refueling strategy is the most optimal, as it generates a higher number of flight cycles. The findings from this study are expected to serve as a foundation for further research on regional aviation in Indonesia, particularly in Kalimantan